Semantic web technologies anchored in learning styles as catalysts towards personalising the learning process. (6th April 2011) - Kerkiri, Tania; Konetas, Dimitris; Paleologou, Angela-M.; Mavridis, Ioannis
The evolution of telecommunications, information and multimedia technologies compel for the design of platforms that support the e-learning processes in a multimodal variety. These platforms benefit from the web resources to enhance their courses. However, the structure of the web is labyrinthine and the facilitation of the learner to the personalised content retrieval in these complex information environments is of great significance. This paper submits a method emerging from the semantic web technologies, such as metadata and ontologies, which is embedded in a constructivist socio-psycho-pedagogical model. The method personalises material based on the alignment of properties of the learning resources and the profile of the e-learners, as derived from their learning style in conjunction with other personality and demographic characteristics. An application is described using an experimental case that exemplifies the proposal. The initial findings justify an optimistic view for future precision in information retrieval and efficient matching of the learners' requirements with the educational content.